Rising to a Challenge? Ten Years of Parliamentary Accountability of the European Semester - Woźniakowski, Tomasz P. (2021)
As a result of the euro crisis, EU economic governance has been reformed and EU institutions have gained new competences regarding national budgets, with the European Semester (the annual cycle of economic surveillance of the member states) being the most prominent example. With the Commission and the Council being the main actors, and the European Parliament playing only a minor role, a debate about the democratic legitimacy of the Semester and the role of national parliaments (NPs) in this regard has unfolded. This thematic issue, therefore, addresses the question of how parliamentary accountability of the European Semester has evolved: Have NPs met the challenge by adapting to the new situation in a way that allows them to hold the executive accountable? While the contributions to this thematic issue show significant variation across NPs, overall they reveal a rather pessimistic picture: Despite several institutional innovations concerning the reforms of internal rules and procedures, the rise of independent fiscal institutions, inter-parliamentary cooperation, and hearings with the European Commissioners, NPs have remained rather weak actors in EU economic governance also ten years after the Semester’s introduction. Whether recent changes linked to the establishment of the Recovery and Resilience Facility introduced in response to the Covid-19 crisis will change the picture significantly remains to be examined.